Modul Sahabat Membaca: Penguatan Literasi Berbasis Pengetahuan Islam pada Gen Alfa di Kuningan Jawa Barat - Dwi Santosa; Rosianna Fitri Fadillah; Iin Suryaningsih (UIN Sunan Kalijaga, 2026)
Abstract - This study is motivated by the low reading interest and literacy skills among students aged 7–12 at MDTA Al-Muqoowim, Kuningan. Initial observations revealed that only 40% of students were able to explain the content of simple reading materials due to conventional teaching approaches that are not yet adaptive to the characteristics of Generation Alpha. To address this issue, the community service program